Shattered selves and border witnessing: globalising trauma studies in Cambodian survivor narratives. Issue 2 (1st February 2021) - Salgado, Minoli
ABSTRACT: Calls to decolonise trauma studies have drawn attention to the need to extend our reading of testimonial narrative beyond the West; to the significance of Cathy Caruth's observation that 'trauma itself may provide the very link between cultures'; and to the importance of generating new critical paradigms that speak to testimonial narratives from the Global South. An analysis of narratives that bear witness to surviving the Cambodian genocide allows for an engagement with a critically-marginalised form of extreme aesthetics and extends our understanding of diasporic border witnessing on and across the threshold of life and death. My evaluation of the witness subject in transnational texts by Loung Ung, Madeleine Thien and Vaddey Ratner reveals the role of borders in the poetics of bearing witness, the significance and value of Khmer readings of grief, loss and suffering, and shows how a culture-specific reading of personhood speaks to both poststructuralist readings and postsecular scriptings of the self. Further, it shows how their soteriological readings of the 'shattered' self work to foreground shared precarity and the interhuman, providing a metaphysical rationale for a re-evaluation of the inscription of bare life in ways that create a space for globalising trauma studies.